2006
DOI: 10.1124/jpet.106.104315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Barley Endoprotease EP-B2 on Gluten Digestion in the Intact Rat

Abstract: Celiac Sprue is a multifactorial disease characterized by an intestinal inflammatory response to ingested gluten. Proteolytically resistant gluten peptides from wheat, rye, and barley persist in the intestinal lumen and elicit an immune response in genetically susceptible individuals. Here, we demonstrate the in vivo ability of a gluten-digesting protease ("glutenase") to accelerate the breakdown of a gluten-rich solid meal. The proenzyme form of endoprotease B, isoform 2 from Hordeum vulgare (EP-B2), was oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 28 publications
2
60
0
Order By: Relevance
“…Microbial prolyl endopeptidases (PEP) detoxify immunodominant gluten in vitro (Shan et al, 2002; Stepniak et al, 2006) and are especially effective when complemented with a barley endoprotease, EP-B2, that preferentially cleaves gluten C-terminal to glutamine residues (Gass et al, 2007; Siegel et al, 2006). The therapeutic promise of these oral proteases is further underscored by their ability to digest gluten in the rat stomach (Gass et al, 2006, 2007) and by the ability of EP-B2 to protect a gluten-sensitive rhesus macaque against gluten-induced clinical relapse (Bethune et al, 2008b). To bring therapeutic glutenases to bear on the human condition of celiac sprue, however, safe and effective tools for assessing enzyme efficacy in human celiac patients are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial prolyl endopeptidases (PEP) detoxify immunodominant gluten in vitro (Shan et al, 2002; Stepniak et al, 2006) and are especially effective when complemented with a barley endoprotease, EP-B2, that preferentially cleaves gluten C-terminal to glutamine residues (Gass et al, 2007; Siegel et al, 2006). The therapeutic promise of these oral proteases is further underscored by their ability to digest gluten in the rat stomach (Gass et al, 2006, 2007) and by the ability of EP-B2 to protect a gluten-sensitive rhesus macaque against gluten-induced clinical relapse (Bethune et al, 2008b). To bring therapeutic glutenases to bear on the human condition of celiac sprue, however, safe and effective tools for assessing enzyme efficacy in human celiac patients are needed.…”
Section: Introductionmentioning
confidence: 99%
“…A Gln-specific cysteine endoprotease B, isoform 2 (EP-B2) from germinating barley seeds is able to rapidly proteolyze gliadin peptides into short polypeptides [36]. Like the fungal and bacterial PEPs, EP-B2 maintains its structure and activity under gastrointestinal conditions [37]. Early proof-of-concept studies demonstrated EP-B2 effectively digested gluten both in the rat stomach and in gluten-sensitive rhesus macaques in a dose- and time-dependent manner [38].…”
Section: Therapies In Clinical Trialsmentioning
confidence: 99%
“…One candidate for protease therapy is EP-B2 (Endoprotease B, Isoform 2), a papain-like cysteine protease that facilitates gluten breakdown and assimilation in germinating seeds of Hordeum vulgare (barley). In vitro and in vivo studies have shown that the zymogen (pro-EP-B2) form of this enzyme rapidly self-activates under gastric conditions, where mature EP-B2 can effectively detoxify gluten at pharmacologically reasonable doses (<5% w/w) Gass et al, 2006). The stage is therefore set for controlled clinical studies to evaluate the utility of this enzyme as supportive therapy for Celiac Sprue patients.…”
Section: Introductionmentioning
confidence: 99%